Question and Answers Forum

All Questions      Topic List

Coordinate Geometry Questions

Previous in All Question      Next in All Question      

Previous in Coordinate Geometry      Next in Coordinate Geometry      

Question Number 39860 by ajfour last updated on 12/Jul/18

Commented by ajfour last updated on 12/Jul/18

OA = BP   , OT =1,   &   ∠OTB = ∠BTP   (given conditions).

OA=BP,OT=1,&OTB=BTP(givenconditions).

Answered by ajfour last updated on 13/Jul/18

((xx_T )/a^2 )+((yy_T )/b^2 )=1   (eq. of tangent at T)  (0, b+a) lies on this tangent  ⇒  y_T = (b^2 /(a+b))        .....(i)  And since (x_T ^2 /a^2 )+(y_T ^2 /b^2 )=1   , hence         x_T ^2  = a^2 −((a^2 b^2 )/((a+b)^2 ))     ...(ii)  As    OT=1  so   x_T ^2 +y_T ^2  = 1     ⇒  a^2 −((a^2 b^2 )/((a+b)^2 ))+(b^4 /((a+b)^2 )) =1  ...(iii)        (a^2 −1)=((b^2 (a^2 −b^2 ))/((a+b)^2 ))  one solution of this eq. is  a=b=1   , otherwise        a^2 −1 = ((b^2 (a−b))/(a+b))       if a=br  then    b^2 r^2 −1=b^2 (((r−1)/(r+1)))      b^2 (r^2 −((r−1)/(r+1)))=1           ...(iv)  And as (  ((PT)/(OT)) = ((BP)/(OB))  )^2   ⇒   ((x_T ^2 +[(a+b)−y_T ]^2 )/1) = (a^2 /b^2 )  ⇒  a^2 −((a^2 b^2 )/((a+b)^2 ))+(a+b)^2 +y_T ^2                           −2(a+b)y_T  = (a^2 /b^2 )  ⇒ a^2 −((a^2 b^2 )/((a+b)^2 ))+(a+b)^2 +(b^4 /((a+b)^2 ))                              −2b^2  = (a^2 /b^2 )      ...(v)  using (iii)  in above eq. (v)       1+(a+b)^2 −2b^2  = (a^2 /b^2 )  again with a=br       1+b^2 (r+1)^2 −2b^2 =r^2   ⇒  b^2 (r^2 +2r−1)=r^2 −1    ...(vi)  comparing (iv) and (vi)  ⇒   ((r^2 +2r−1)/(r^2 −((r−1)/(r+1)))) = ((r^2 −1)/1)  ⇒    ((2r)/(r^2 −1−((r−1)/(r+1)))) = r^2 −1   2r(r+1)=(r^2 −1)[(r^2 −1)(r+1)−(r−1)]  ⇒  2r=(r−1)^2 [(r+1)^2 −1]  ⇒   2r = (r^2 −1)^2 −(r−1)^2   or   r^4 −3r^2 =0  ⇒    r= (√3)      (valid answer)     Now from (vi) we have     b^2  = ((r^2 −1)/(r^2 +2r−1)) = (2/(2+2(√3))) = (1/(1+(√3)))     = (((√3)−1)/2)     While  a^2  = b^2 r^2  = ((3((√3)−1))/2)  Ellipse eq. is thus        ((2x^2 )/(3((√3)−1)))+((2y^2 )/((√3)−1)) =1  or     _(______________________)              2x^2 +6y^2  = 3(√3)−3            ^(   _______________________ .)

xxTa2+yyTb2=1(eq.oftangentatT)(0,b+a)liesonthistangentyT=b2a+b.....(i)AndsincexT2a2+yT2b2=1,hencexT2=a2a2b2(a+b)2...(ii)AsOT=1soxT2+yT2=1a2a2b2(a+b)2+b4(a+b)2=1...(iii)(a21)=b2(a2b2)(a+b)2onesolutionofthiseq.isa=b=1,otherwisea21=b2(ab)a+bifa=brthenb2r21=b2(r1r+1)b2(r2r1r+1)=1...(iv)Andas(PTOT=BPOB)2xT2+[(a+b)yT]21=a2b2a2a2b2(a+b)2+(a+b)2+yT22(a+b)yT=a2b2a2a2b2(a+b)2+(a+b)2+b4(a+b)22b2=a2b2...(v)using(iii)inaboveeq.(v)1+(a+b)22b2=a2b2againwitha=br1+b2(r+1)22b2=r2b2(r2+2r1)=r21...(vi)comparing(iv)and(vi)r2+2r1r2r1r+1=r2112rr21r1r+1=r212r(r+1)=(r21)[(r21)(r+1)(r1)]2r=(r1)2[(r+1)21]2r=(r21)2(r1)2orr43r2=0r=3(validanswer)Nowfrom(vi)wehaveb2=r21r2+2r1=22+23=11+3=312Whilea2=b2r2=3(31)2Ellipseeq.isthus2x23(31)+2y231=1or______________________2x2+6y2=333_______________________.

Commented by tanmay.chaudhury50@gmail.com last updated on 13/Jul/18

bah...very good...excellent...

bah...verygood...excellent...

Commented by ajfour last updated on 13/Jul/18

thanks sir !

thankssir!

Commented by MrW3 last updated on 13/Jul/18

awesome!

awesome!

Terms of Service

Privacy Policy

Contact: info@tinkutara.com